Book Review: The Bead Maker From Ribe: The Story of a Viking Craftsman by Thomas Risom - Neil Peterson (EXARC Journal)
Having been involved with experimental work with Viking Era beads for a decade and a half, I am always looking for more information on the topic. Ribe is the most significant beadmaking site of the Viking Era due to its archaeological remains and the museum’s active experimental, interpretative, and craft programs. New material focusing on this site is thus of particular interest, so I was very pleased to get a copy of Thomas Risom’s The Bead Maker from Ribe.